Linking Social Investment in Education and Health to Labor Productivity: The Case of Vietnam - Khang, Nguyen The (Journal of Posthumanism, 2025)
This study aims to evaluate the impact of investment in the education and healthcare sectors on labor productivity in Vietnam from 2000 to 2023. Grounded in human capital theory and the endogenous growth model, this study employs the Autoregressive Distributed Lag approach to examine both the short- and long-run relationships among key macroeconomic variables, including investment in education, investment in healthcare, foreign direct investment, and labor productivity. The empirical findings reveal that in the long run, investment in both education and healthcare exerts a positive influence on labor productivity. Specifically, investment in education is statistically significant at the 5% level, whereas healthcare investment is significant at the 10% level. Conversely, foreign direct investment does not exhibit a statistically significant effect on labor productivity in the long term. In the short run, education investment continues to show a positive and significant impact, whereas the effects of healthcare investment and foreign direct investment are positive, but not statistically robust. The error correction coefficient is negative and statistically significant, indicating a relatively rapid adjustment speed of 74.18% per year toward long-run equilibrium. The diagnostic tests confirmed the validity and reliability of the model. This study highlights the critical role of education and healthcare in enhancing labor productivity and recommends that the government prioritize strategic budget allocation and improve the efficiency of public investment to foster sustainable economic growth.